PURWARUPA SISTEM PENDETEKSI JARAK ANTAR QUADROTOR DENGAN SENSOR GPS - Esa Apriaskar (POLITEKNIK NEGERI BENGKALIS, 2018)
Technology of UAV (Unmanned Aerial Vehicle) which is quite rapidly developing in recent years, is quadrotor. The increasing number of quadrotor utilization in various aspects of life is one of the factors driving the development of research on quadrotor technology. The ability of a quadrotor to determine its distance from other quadrotor is one of the important factors that can support the success of formation swarm of quadrotor. This research aimed to create a prototype of distance detection system capable of supporting the mission of the formation swarm of quadrotor. Two pairs of latitude and longitude angles data from GPS sensor which represented coordinate position of 2 quadrotors were calculated using haversine formula to get the distance between 2 quadrotors. Data resulted from the system are compared with actual distance to test the success of the system in calculating the distance between two quadrotor distance.